PENERAPAN UNSUR PERMUFAKATAN JAHAT PADA PENYIDIKAN TINDAK PIDANA NARKOTIKA (Studi Pada Satres Narkoba Polresta Padang) - Syah, Herit (Universitas Ekasakti, 2020)
Bad conspiracy in Law Number 35 Year 2009 concerning Narcotics can be seen in Article 1 number 18 and Article 132 Paragraph (1) Investigation of conspiracy in narcotics crime requires evidence that shows an agreement. This research is a legal research with analytical descriptive specifications. The application of the element of bad consensus in the investigation of narcotics crime by investigators of the Padang Police Narcotics Investigation is to collect evidence so that it meets the elements of the existence of a trial / consensus, to commit narcotics crime as in the case with Police Report No. Pol: LP / 17 / IX / A / 2019 / Ta, October 27, 2018. Obstacles and Efforts to Overcome It in the Application of Criminal Consensus Elements in Narcotics Crimes by Investigators at the Narcotics of Padang Police Narcotics is the lack of equipment needed, the limited operational costs of the process investigation, it is difficult to get informants / espionage.